An intraluminal jejunal gastrointestinal stromal tumor near DJ flexure with gastrointestinal bleed: a rare case report - Bansal, Manish; Gupta, Sameer; Goel, Kanika; Mittal, Sulbha (International Surgery Journal, 2017)
Gastrointestinal stromal tumours (GISTs) are mesenchymal tumors arising in the gastrointestinal tract (GIT). In GIT, the most common site of presentation is stomach followed by small intestine, colon, rectum and oesophagus. Here we report a rare case of intraluminal jejunal GIST with history of pain abdomen, occasional vomiting and GI bleed. Patient was taken up for exploratory laparotomy. Intraoperative findings revealed a hard-nodular growth in antimesenteric border of jejunum, 5 cm distal to duodenojejunal flexure (DJ) partially obstructing the lumen. Anastomosis was quite difficult due to presence of growth near DJ flexure and chances of leak were high. The patient had an uneventful postoperative course and doing well after 1 year of follow up with no recurrence.